2014
DOI: 10.3109/13880209.2014.928330
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants contain mucilage used in traditional Persian medicine (TPM)

Abstract: A scientific evaluation of these historical documents can give an insight into the ideas of the past and be valuable in finding new data on clinical use of the mucilages that should lead to future opportunities to investigate their potential medicinal use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 91 publications
0
36
0
Order By: Relevance
“…114 This is not correct because it refers to "Mulukhiyah" or Corchorus olitorius, a plant in the Malvaceae family but to the genus Corchorus not Malva.…”
Section: Discussionmentioning
confidence: 99%
“…114 This is not correct because it refers to "Mulukhiyah" or Corchorus olitorius, a plant in the Malvaceae family but to the genus Corchorus not Malva.…”
Section: Discussionmentioning
confidence: 99%
“…In Persian medicine, A.digitata was used to heal the coughs (specially for coughs due to irrigation and inflammation of pharyngeal mucosa) to decrease the swelling of mucus membranes of stomach and intestines, inflations of brain, ears and eyelids, to heal the wounds, and to relief the pain of swellings and wens (15,16). Approved indications and usages of this herb by commission E are cough and bronchitis, inflammation of gastric mucosa, oral, and pharyngeal irritation (17).…”
Section: Objectivesmentioning
confidence: 99%
“…it is also useful in treatment of inflammations of respiratory, urinary and digestive tracks, and acnes. Studies show that this herb has antibacterial, antifungal, and antiviral effects against human pathogens (16,19). It was shown that the aqueous extract of M.sylvestris is more effective than cimetidine in treatment of gastric ulcers (18,20).…”
Section: Objectivesmentioning
confidence: 99%
“…Every humor is a matter produced from the transformation of foodstuff in the digestive system. From the perspective of ITM, health depends on the balance of these humors, and an abnormality or imbalance of these humors can lead to illness (14,15).…”
Section: History and Principles Of Itmmentioning
confidence: 99%